2015
DOI: 10.1590/0102-311x00090514
|View full text |Cite
|
Sign up to set email alerts
|

The socio-spatial context as a risk factor for hospitalization due to mental illness in the metropolitan areas of Portugal

Abstract: This study's aims are: (i) identifying spatial patterns for the risk of hospitalization due to mental illness and for the potential risk resulting from contextual factors with influence on mental health; and (ii) analyzing the spatial association between risk of hospitalization due to mental illness and potential risk resulting from contextual factors in the metropolitan areas of Lisbon and Porto, Portugal. A cross-sectional ecological study was conducted by applying statistical methods for assessing spatial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
4
1
Order By: Relevance
“…Higher isolation, poor transportation and communications, difficulties to access health and social services are potentially risky conditions for mental health (Loureiro et al, 2015); even though in our study we found a lower percentage of dementia in the rural sample, it should be object of further attention.…”
Section: Discussioncontrasting
confidence: 60%
“…Higher isolation, poor transportation and communications, difficulties to access health and social services are potentially risky conditions for mental health (Loureiro et al, 2015); even though in our study we found a lower percentage of dementia in the rural sample, it should be object of further attention.…”
Section: Discussioncontrasting
confidence: 60%
“…Previous studies also identified the presence of inequalities within these metropolitan areas, although at a more detailed scale [29,35,51]. For example, in the Lisbon case, geographic disparities between municipalities are not evident as expected, considering other studies on health inequalities at the small area level [19,21,27].…”
Section: Discussionmentioning
confidence: 87%
“…High levels of intra-urban inequalities are also visible as a result of the demographic, economic, environmental, and other societal challenges impacting cities, along with a greater population heterogeneity and different level of access to housing, amenities and services [2,10,13,26]. According to the literature, poor and vulnerable groups are often more at risk due to the concentration on disadvantaged and deprived neighbourhoods, usually in the outskirts of the city or in inner city areas [27,28,29,30]. The Atlas of Population Health in European Union Regions [31], shows that the capital region of each EU country ussually performs better in health determinants (e.g., economic and social conditions, healthcare resources) than in health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Differences regarding the demographic, economic, and environmental characteristics, the different level of access to housing, amenities, and services, and to other societal challenges impacting cities explain the presence of intra-urban inequalities [7,8]. Considering previous studies on European cities, socioeconomic inequalities in health continue to be of greater magnitude in more urbanized communities, where vulnerable people are clustered in impoverished neighborhoods and deprived areas, usually in the suburbs of the city or in inner city areas [9][10][11]. Costa et al [12] observed that municipalities performing worse in health determinants also present worse health outcomes.…”
Section: Introductionmentioning
confidence: 99%